Developing Scholarship of Teaching and Learning through a Community of Enquiry - Bozalek, Vivienne; Dison, Arona; Alperstein, Melanie; Mitchell, Veronica (Critical Studies in Teaching and Learning, 2023)
A growing interest in the Scholarship of Teaching and Learning (SoTL) in higher education requires the seeking of opportunities for its development within and across disciplines and institutions. However, rewards for individual competitiveness in research publications, including the Scholarship of Teaching and Learning (SoTL), tend to discourage collaboration, which could be highly conducive to the development of SoTL. This paper proposes the value of working together in a collaborative community of enquiry (CoE) in order to take forward SoTL in higher education. We draw on Cassidy et al.’s (2008) and Christie et al.’s (2007) model of seven elements of a CoE to explore our own experience of forming a CoE emanating from an inter-institutional professional course on teaching and learning, which assisted us to collaboratively contribute to SoTL. The above model was found to be useful, but could be enhanced through an expanded perspective, incorporating the affective turn.